Diagnosing oral squamous cell carcinoma: How much imaging do we really need? A review of the current literature. Issue 5 (May 2016) - Blatt, Sebastian; Ziebart, Thomas; Krüger, Maximilian; Pabst, Andreas Max
Abstract: Complementary imaging techniques that round out the clinical examination are fundamentally important in the work-up of patients with oral squamous cell carcinoma (OSCC). Above all, exact determination of primary tumour extent, metastatic spread, and treatment response highly depend on accurate imaging methods. Despite a multitude of recently published reviews, there is still an ongoing debate regarding the best imaging method. In order to update the current literature with the latest evidence, a systematic literature search via Pubmed was performed. In total, 56 studies were enrolled, 4170 patients were analysed, and twenty different imaging methods were evaluated referring to their sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV). In summary, CT (computed tomography) and MRI (magnetic resonance imaging) currently remain the gold standard for evaluating extension of the primary tumour site. No additional evidence could be obtained for functional imaging methods displaying metastatic spread in the cervical lymph nodes, but was found for distant metastases. Furthermore, functional imaging seems to be beneficial in evaluating treatment response. There is further evidence in the accuracy of the different imaging methods found in this update that could possibly be implemented into the revision of the current guidelines and obtain a clear and coherent approach in the clinical set-up.